2017
DOI: 10.1057/s41274-016-0149-4
|View full text |Cite
|
Sign up to set email alerts
|

A literature review on dynamic pricing of electricity

Abstract: Revenue management and dynamic pricing are concepts that have immense possibilities for application in the energy sector. Both can be considered as demand-side management tools that can facilitate the offering of different prices at different demand levels. This paper studies literature on various topics related to the dynamic pricing of electricity and lists future research avenues in pricing policies, consumers' willingness to pay and market segmentation in this field. Demand and price forecasting play an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
114
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(117 citation statements)
references
References 81 publications
1
114
0
2
Order By: Relevance
“…Fuel cost Cost F g;t to procure energy fromg th thermal generating unit in hour t is given by Equation (6), subject to constraints (6) to (14). The piece-wise linearization of the quadratic cost function is given in Appendix A.…”
Section: Thermal Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Fuel cost Cost F g;t to procure energy fromg th thermal generating unit in hour t is given by Equation (6), subject to constraints (6) to (14). The piece-wise linearization of the quadratic cost function is given in Appendix A.…”
Section: Thermal Generationmentioning
confidence: 99%
“…Market prices are dynamic in nature and vary throughout the day. 6 Consumer response to offered sale prices depends on its elasticity, indicating consumption change in response to price change. 3 A popularly evolving dynamic pricing mechanism, Time of Use (ToU) pricing motivates consumers to shift their demand from high to low price periods.…”
Section: Introductionmentioning
confidence: 99%
“…However, fluctuation in wholesale electricity prices has increased because of the intermittent nature of generation from RESs [1]. By contrast, the retail market generally offers flat pricing or block pricing, because customers cannot continuously respond to price fluctuations [2]. Therefore, retailers who secure energy in the wholesale market to serve the demand of customers face price risks caused by the difference between wholesale prices and retail rates.…”
Section: Introductionmentioning
confidence: 99%
“…Such tariff has been used in utility companies in the USA [10,11]. Furthermore, a dedicated review of dynamic electricity pricing can be found in [12].…”
Section: Introductionmentioning
confidence: 99%